Fidelity and The Gendered Translation - Arrojo, Rosemary (TTR, 1994)
AbstractFidelity and The Gendered Translation — Postmodern theories of language have drastically changed the ways we view the translator's task and the relationships that can be established between the so-called original and its foreign versions. One of the most important insights brought about by such textual theories is the recognition of the translator's inescapable authorial role in the translated text. At the same time, an increasing awareness of the impact of gender-related issues to the production of meaning is beginning to encourage a promising union between feminism, contemporary textual theories, and the emerging discipline of translation studies. Such a union has begun to produce a new brand of politically motivated translations as well as an enlightening reflection on the issues of both translation and gender and to prompt some female translators to write about their feminist practice and strategies that explicitly subvert the original they disagree with. However, as I intend to argue, even though their work and theoretical comments do reveal that their voices have already conquered a much deserved space within the (still) predominantly essentialist scenario of patriarchal culture, they seem to be repeating some version of the same scenario which treats original and translations differently and which they rightly condemn in traditional theories of translation and gender. As they disguise their conscious intervention in the text they translate under the mask of some form of or to the same original they explicitly deconstruct, such translators fail to take their own sound insights seriously and run the unnecessary risk of jeopardizing their work.